Watching sports events and residents’ subjective well-being: evidence from the CGSS and the potential roles of health and social capital - Wei, Xuemeng; Zhao, Shutong (Frontiers in Psychology, 2026)
IntroductionInvestigating the association between watching sports events and residents’ subjective well-being and the potential mediating mechanisms advances understanding of the positive psychological correlates of sports spectatorship and provides a basis for efforts to support well-being and promote social harmony.MethodsBased on 8 years of the Chinese General Social Survey (CGSS) data spanning 2010–2023, we employed OLS regressions with province and survey-year dummy variables, Ordered Probit and Ordered Logit regressions, and propensity score matching (PSM) to examine the association between watching sports events and subjective well-being. We also tested whether health capital and social capital statistically accounted for part of this association.ResultsWatching sports events was positively associated with subjective well-being, and the association remained after heterogeneity analyses and selection-adjustment checks. The association was strongest in the West, followed by the Central and the East. It was significant for men but not for women. By education, the association was largest among high-school-educated residents, smaller but significant among those with college and above, and not significant among those with primary or lower-secondary education. Mediation analyses were consistent with social capital (social class, social trust, and social support) and physical health, statistically accounting for part of the association between watching sports events and subjective well-being; by contrast, mental health did not emerge as a primary statistical pathway.ConclusionThese results advance knowledge of how watching sports events relates to well-being and offer policy-relevant insights for promoting happiness through accessible, low-cost leisure engagement, while also acknowledging potential downsides of excessive viewing.